Multi-event modeling of true reproductive states of individual female right whales provides new insights into their decline - Reed, Joshua; New, Leslie; Corkeron, Peter; Harcourt, Robert (Frontiers in Marine Science, 2022)
Abundance and population trends of Critically Endangered North Atlantic right whales (Eubalaena glacialis, NARW) have been estimated using mark-recapture analyses where an individual’s state is based upon set delineations of age, using historical estimates of age at first reproduction. Here we assigned individual females to states based upon their reproductive experience, rather than age. We developed a Bayesian mark-recapture-recovery model to investigate how survival, recapture, site-fidelity and dead-recovery probabilities vary for female NARW in different states, using data collected from 1977-2018. States were assigned as calves for individuals in their first year; pre-breeder for individuals greater than one year of age who had yet to produce a calf, or breeder if an individual had reproduced. A decline in abundance of female NARW was seen starting in 2014, with 185 females declining yearly to 142 by 2018. The largest decline was seen in breeding females, with 72 estimated to be alive at the beginning of 2018, while female pre-breeder abundance plateaued at around 70 between 2011- 2018. Females born from 2000 onwards had an average 4% (95% CI:0.03-0.06) chance of transitioning from pre-breeder to breeder, compared to 8% (95%CI:0.06-0.1) for females born prior. This reduction in transition rate from non-breeder to breeder for the current cohort resulted in breeding females declining to 51% of the female population by 2018. We show that a collapse in fecundity of breeding females, and the failure of pre-breeders to start breeding, is an important factor in understanding the current decline in abundance of the NARW.